텐서플로 기반 딥러닝 수업 모형 개발 - 강환수(Hwan-Soo Kang); 조진형(Jin-Hyung Cho); 김희천(Hee-Chern Kim) (디지털콘텐츠학회논문지, 2022)
최근 학교 교육에서 인공지능의 기초지식을 요구하는 인공지능 리터러시의 중요성이 강조되고 있다. 국내 고등학교에서도 인공지능 수학과 기초를 선택과목으로 운영하고 있다. 본 연구에서는 2년제 대학의 컴퓨터 관련 전공 학생 대상으로 텐서플로 기반 딥러닝 수업 모형을 개발하고 이 모형을 실제 수업에 운영하여 대응표본 t-검정을 시행해 효과성을 검증하였다. 수업 모형의 학습역량 효과성 검증을 위해 ‘깃허브와 코랩 활용’과 ‘인공지능과 딥러닝의 이해’, 그리고 ‘텐서플로 기반 딥러닝 구현’의 학습역량을 도출하고 이를 대응표본 t-검정으로 분석하였다. 연구의 수업 모형을 적용한 수업에서 사전·사후 검사를 통해 딥러닝에 관한 학생의 역량이 향상되었다는 유의미한 결과를 얻었다. Recently, the importance of artificial intelligence literacy, which requires basic knowledge of artificial intelligence, has been emphasized in school education. In Korean high schools, artificial intelligence mathematics and basics are operated as elective subjects. In this study, a tensorflow-based deep learning teaching model was developed for computer-related students at a two-year college university, and this model was operated in actual classes to verify the effectiveness by a paired t-test. In order to verify the effectiveness of the learning competency of this model, the learning competencies of ‘Utilization Colab and GitHub’, ‘Understanding AI, ML(Machine Learning) and deep learning’ and ‘Implementing deep learning based on Tensorflow’ were derived and analyzed with paired t-test. A significant result was obtained that students' competence in deep learning was improved through pre and post tests applying the study's teaching model. KCI Citation Count: 1